Ovarian sclerosing stromal tumour: Report of a new entity with immunohistochemical study. - Rahman, Papiya; Afroz, Sadia; Shabnam, Ummey Salma; Nesa Emita, Umama Tun; Dey, Bishnu Pada; Begum, Ferdousy (Bangladesh Journal of Medical Science, 2023)
Sclerosing stromal tumour (SST) is a rare benign sex cord stromal tumour occurring in women in their second and third decades. Patients usually present with menstrual irregularity and pelvic pain. Microscopically, this tumour is characterized by epithelioid and spindle cells arranged in pseudolobules separated by areas with fibrous deposition of various amount. Presence of ‘staghorn like’ proliferating vasculature is the hallmark feature of this tumour. The main differential diagnoses are thecoma and fibroma. Immunohistochemistry can be used to differentiate these tumours. This relatively new entity should be kept in mind while reporting ovarian tumour in a young female. We have described SST in an 18 year old female in this case report. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 712-717